Adaptive Multi-Resolution Method for 3D Reactive Flows with Level Set Front Capturing (Communications in Computational Physics, 2023)
For compressible reactive flows with stiff source terms, a new block-basedadaptive multi-resolution method coupled with the adaptive multi-resolution representation model for ZND detonation and a conservative front capturing method basedon a level-set technique is presented. When simulating stiff reactive flows, underresolution in space and time can lead to incorrect propagation speeds of discontinuities, and numerical dissipation makes it impossible for traditional shock-capturingmethods to locate the detonation front. To solve these challenges, the proposed methodleverages an adaptive multi-resolution representation model to separate the scales ofthe reaction from those of fluid dynamics, achieving both high-resolution solutionsand high efficiency. A level set technique is used to capture the detonation frontsharply and reduce errors due to the inaccurate prediction of detonation speed. Inorder to ensure conservation, a conservative modified finite volume scheme is implemented, and the front transition fluxes are calculated by considering a Riemann problem. A series of numerical examples of stiff detonation simulations are performed toillustrate that the present method can acquire the correct propagation speed and accurately capture the sharp detonation front. Comparative numerical results also validatethe approach’s benefits and excellent performance.
Keywords: Compressible reactive flows; reactive Euler equations; three-dimensional simulation; adaptive multi-resolution; level set method; sharp front capturing.